Efikasi Asap Cair Dari Limbah Pengolahan Industri Gondorukem Pada Kayu Karet Terhadap Rayap Kayu Kering (Cryptotermes cynocephalus Light.) - Ghani Fakkar; Ihak Sumardi; Suhaya, Yoyo (Jurnal Penelitian Hasil Hutan, 2023)
Wood vinegar is made from condensation of biomass pyrolysis, contained phenolic compound, carbonyl, and acid that used for insecticide, wood and food preservative, and aroma enhancer. Pine waste as biomass obtained from gum rosin and turpentine processing had a great potential to be processed into wood vinegar. This paper studies the effect of coating rubber wood using wood vinegar made from pine waste against dry-wood termite. The rubber wood (2.5x2.5x5 cm3) was coated with distillated and without distilled (crude) wood vinegar in 100, 50, and 25% dilution. Samples were conditioned within in hours before PVC pipes (2.6 cm diameter and 5 cm height) were installed into wood surface using wax. There were 50 drywood termite fed into the pipes. The samples kept in dark room for 12 weeks. This experiment was conducted according to SNI 01-7207-2014. The result showed that coating method using un-distilled or crude wood vinegar made from pine waste could increase the durability of rubber wood against dry-wood termite. This happened due to the toxic compound in the crude wood vinegar that made coating methods using un-distilled wood vinegar can be used to increase the durability of rubber wood against dry-wood termite.